2015
DOI: 10.1001/jama.2014.17426
|View full text |Cite
|
Sign up to set email alerts
|

Resective Epilepsy Surgery for Drug-Resistant Focal Epilepsy

Abstract: Epilepsy surgery reduced seizure activity in randomized clinical trials when compared with continued medical therapy. Long-term cognitive, psychiatric, psychosocial, and quality-of-life outcomes were less well defined. Despite good outcomes from high-quality clinical trials, referrals of patients with seizures refractory to medical treatment remain infrequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
344
3
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 522 publications
(373 citation statements)
references
References 64 publications
18
344
3
8
Order By: Relevance
“…A recent review found that extratemporal versus temporal surgery was inconsistently associated with outcome 30. Overall, it appears that extratemporal surgery is associated with less chance of long-term remission than is temporal lobe surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review found that extratemporal versus temporal surgery was inconsistently associated with outcome 30. Overall, it appears that extratemporal surgery is associated with less chance of long-term remission than is temporal lobe surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3 Though the overall risk of morbidity has been low (8%-10.8%), TLE surgery has been associated with medical and neurologic complications. Medical complications include CSF leak (5.8%), aseptic meningitis (2.7%), pneumonia (0.7%), intracranial hematomas (1.5%), deep vein thrombosis/pulmonary embolism (0.7%), and hydrocephalus (1.4%).…”
Section: Oy-stersmentioning
confidence: 99%
“…Definitions such as the ILAE definition are necessary, but drug-resistant severe generalized tonic-clonic seizures certainly call for more treatment than drug-resistant focal seizures without objective manifestations. Epilepsy remains a dynamic disease with spontaneous fluctuations in seizure occurrence, which makes it so difficult to determine outcomes (5). The desire to consider just a one-time intervention and report the associated outcome may not fit the nature of the disease (6).…”
Section: Consensus Over Individualism: Validation Of the Ilae Definitmentioning
confidence: 99%